Attributes of migratory goat and sheep farming and impact of some improved management strategies en-route migration in adopted flocks of Western – Himalayan region of India - SANKHYAN, VARUN; DOGRA, PARDEEP KUMAR; THAKUR, Y P (The Indian Journal of Animal Sciences, 2016)
Migratory pastoralism is common in Himalayas, practiced by Gaddi tribe of Himachal Pradesh. Understanding migratory system is relevant as >90% of state sheep and around 70 % goat populations is reared under this system. The study was undertaken to analyse characteristics, trends, constraints and impact assessment of improved managemental strategies enroute migration. After generation of base data, for studying the impact of improved practices and breeding management, these flocks were monitored and strategic managemental and breeding inputs were provided to these flocks throughout the year for next 3 years. Majority of the farmers belonged to medium flocks (50%), followed by small flocks (40.2%) while very few were with larger size flock (9.8%). On an average, these farmers derived more than 60% of their income of migratory goat and sheep husbandry. Farmer’s own flock was the primary source (68.4%) of breeding buck and they practice selection of male buck based on indigenous knowhow. Diseases, predators, environmental extreme, veterinary aid in high hills and marketing infrastructure were major constraints. The result of adopted flock over period of 4 year revealed that there was significant improvement in body weight, reproductive parameters and pre-weaning mortality. The study concluded that the migratory system is an integral part of hill farming and is sustainable since it is a very low input system which effectively counterbalances its constraints and makes it profitable. There is need to address concern of management during migration, develop effective extension messages and breeding plans.